426 COMPUTER-ASSISTED COUNSELING AND RAPID HIV SELF-TESTING IN CHEMICAL DEPENDENCY TREATMENT SETTINGS. Issue 1 (1st January 2007) - Bui, K.; Spielberg, F.
Abstract : Background: Approximately 25% of 900, 000 people infected with HIV in the United States do not know that they are infected. Drug treatment settings are ideal places to reach populations at risk; however, few have the capacity to offer on-site HIV counseling and testing. We have developed an interactive computer counseling tool (CARE) that may make HIV testing in drug treatment settings feasible. This study aims to assess the acceptability and usability of the CARE tool with HIV rapid self-testing among staff at a drug treatment center. Study Design and Methods: Focus groups were conducted in three chemical dependency treatment settings: detoxification ( N = 13), inpatient ( n = 7), and outpatient ( n = 7). Information on current HIV counseling and testing practice and feedback on computer-assisted counseling and rapid self-testing was obtained. Qualitative data were analyzed by three coders using iterative content analysis. Results: Each treatment setting reported a unique system of HIV risk assessment and education. HIV testing is only offered on a limited basis by an outside organization. Staff reported that challenges to their current practice are limited risk disclosure, need for effective HIV education, and competing priority of the chemical dependency treatment mission. Perceived limitations of the CARE tool included concerns that some clients will not be literate enough to use the tool, conflict over the role that computers should have in counseling, concern about distracting clients from their chemical dependency treatment goals, low impact of the CARE tool given a resistant client population, and administrative concern regarding documentation requirements. Perceived strengths of the CARE tool included novelty, enhanced client disclosure, and ability for use among low-literacy populations. Staff believed that the CARE tool may provide enhanced HIV education and new opportunities for HIV counseling and testing that is private and personalized. Staff thought that the tool may promote the chemical dependency mission by increasing client responsibility. Incentive was expressed as important to the acceptability of the CARE tool among clients. Staff suggested improvements to the tool, such as making characters and scenarios in the skill-building videos more consistent with the needs and demographics of their population. Conclusion: With modifications, the CARE tool may have a role in expanding access to HIV counseling and testing in chemical dependency treatment settings. A study is now ongoing to test the acceptability and usability of computer assisted self-testing in these three treatment settings.